2023
DOI: 10.1111/gcb.16593
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal patterns of forest ecosystem stability across spatial scales as affected by biodiversity and environmental heterogeneity

Abstract: Our planet is facing a variety of serious threats from climate change that are unfolding unevenly across the globe. Uncovering the spatial patterns of ecosystem stability is important for predicting the responses of ecological processes and biodiversity patterns to climate change. However, the understanding of the latitudinal pattern of ecosystem stability across scales and of the underlying ecological drivers is still very limited. Accordingly, this study examines the latitudinal patterns of ecosystem stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 120 publications
0
7
1
Order By: Relevance
“…Another notable finding of our study is that herbivore exclusion increased spatial asynchrony but not beta diversity among local communities, which is at odds with that of several recent studies (Chen et al., 2022; Liang et al., 2021; Qiao et al., 2023). The lack of treatment effect on beta diversity in our experiment likely reflects the fact that the same species (e.g., K. pygmaea and S. purpurea ) attained dominance both in the presence and absence of grazers (Figure S6), despite grazing acting to reduce the relative abundance of these dominant species in the unfenced plots.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Another notable finding of our study is that herbivore exclusion increased spatial asynchrony but not beta diversity among local communities, which is at odds with that of several recent studies (Chen et al., 2022; Liang et al., 2021; Qiao et al., 2023). The lack of treatment effect on beta diversity in our experiment likely reflects the fact that the same species (e.g., K. pygmaea and S. purpurea ) attained dominance both in the presence and absence of grazers (Figure S6), despite grazing acting to reduce the relative abundance of these dominant species in the unfenced plots.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of treatment effect on beta diversity in our experiment likely reflects the fact that the same species (e.g., K. pygmaea and S. purpurea ) attained dominance both in the presence and absence of grazers (Figure S6), despite grazing acting to reduce the relative abundance of these dominant species in the unfenced plots. While a positive relationship between beta diversity and spatial asynchrony has been predicted by theory (Wang & Loreau, 2014, 2016), and supported by several empirical studies (Liang et al., 2022; Qiao et al., 2023; Wang et al., 2020), the lack of the relationship between the two has also been reported (Wilcox et al., 2017; Zhang et al., 2019). We suggest that the greater spatial asynchrony among local communities under herbivore exclusion likely arose from increased stochastic dynamics of subordinate and rare species (e.g., Gentiana scabra , Oxytropis stracheyana , Trisetum spicatum ) when facing stronger competition from more abundant, dominant plants (Alberti et al., 2017; Segre et al., 2014).…”
Section: Discussionmentioning
confidence: 73%
“…Data are available from the Figshare Digital Repository: https:// doi.org/10.6084/m9.figshare.23683395 (Qiao et al 2023).…”
Section: Author Contributionsmentioning
confidence: 99%
“…Recently, with the changing global environment, the interactions between ecosystem processes and environmental drivers have attracted significant attention ( Hautier et al., 2015 ; White et al., 2022 ; Qiao et al., 2023 ). Specific environmental drivers may cause long-term impacts on ecosystem functions and sustainability, and exhibit greater spatial heterogeneity with geographic gradients ( Loarie et al., 2009 ; Nishizawa et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Climate stability during the growing season is critical for maintaining biodiversity and ecosystem functioning in drylands ( Souza et al., 2016 ; Lu et al., 2019 ). Studies have found that climate stability could affect community functioning by reducing both SD-alpha and SD-beta in temperate grasslands ( Zhang et al., 2019 ), and another study has shown that climate stability is driven by longitude in forest ecosystems ( Qiao et al., 2023 ). (iii) Climate seasonality is believed to be an underestimated factor affecting ecosystem functioning at the macro scales ( Liang et al., 2022 ; Du et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%